Pulse Oximetry Using Organic Optoelectronics under Ambient Light. Issue 5 (6th March 2020) - Han, Donggeon; Khan, Yasser; Ting, Jonathan; Zhu, Juan; Combe, Craig; Wadsworth, Andrew; McCulloch, Iain; Arias, Ana C.
Abstract: Light absorption in oxygenated and deoxygenated blood varies appreciably over the visible and near‐infrared spectrum. Pulse oximeters use two distinct wavelengths of light to measure oxygen saturation SpO2 of blood. Currently, light‐emitting diodes (LEDs) are used in oximeters, which need additional components to drive them and negatively impact the overall size of the sensor. In this work, an ambient light oximeter (ALO) is demonstrated, which can measure photoplethysmography signals and SpO2 using various kinds of ambient light, avoiding the use of LEDs. Spectral filters are combined with organic photodiodes to create the ALO with sensitivity peaks at green (525 nm), red (610 nm), and near‐infrared (740 nm) wavelengths. Finally, the wearable ALO is used to measure photoplethysmography signals and SpO2 on the index finger in different indoor and outdoor lighting conditions and the measurements are validated with commercial pulse oximeters under normal and ischemic conditions. Abstract : Pulse oximetry is performed under ambient light using flexible sensors. Pulse oximetry requires spectral selectivity. Normally, this is achieved by having two different light‐emitting diodes with different spectrum. Here, flexible organic photodiodes with commercially available color filters are used to achieve spectral selectivity. With this configuration, ambient lighting is utilized to perform photoplethysmography. Then, pulse oximetry performs under the Sun.